Training With Direct Versus Indirect Spatial Stimulus–Response Compatibility in Combat Sports. Issue 4 (August 2020) - Luis del Campo, Vicente; Pajuelo Miranda, Jose Manuel; Morenas Martín, Jesús
The study examined effects of spatial stimulus–response compatibility on response time and response accuracy in 20 novice combat sport athletes. Two equivalent groups, based on initial reaction time measures, were required to perceive and move quickly and accurately in response to an unspecific visual stimulus presented on a large screen during the two types of perceptual training in eight laboratory sessions. One group reacted by moving the fist toward the stimulus location on the target (direct compatibility condition). Another group was required to move the fist away from target in the opposite direction (indirect compatibility condition). Specifically, the indirect compatibility group achieved faster reaction times than the direct compatibility group during the two posttests containing video-projected attacks of the opponents, and in one of the two posttests containing real opponents' attacks. Results seem to reveal higher combat performance against real opponents when athletes trained with an indirect stimulus–response compatibility condition.